Pengaruh Bahasa Tionghoa Terhadap Bahasa Sehari-hari - Mikhail Perdana; Rudiansyah Rudiansyah (Jurnal Bahasa, Sastra, dan Budaya, 2021)
The existence of citizens of Chinese descent has been recognized by the Indonesian population, especially residents of Jakarta. Since hundreds of years ago, the ethnic Chinese population has lived in Jakarta, socializing, and socializing closely with the natives. It also affects the history and culture in Jakarta, for example, the style of buildings, food, speech, and clothing. The most noticeable is the use of words that we often use every day. For example, the use of the words "lu" and "gue" turns out to be derived from the dialect family of languages spoken by the Chinese in the Fujian area. People from Fujian who are of Chinese descent dominate in Indonesia. The culture in Fujian is called Minnan or Southern Min or Hokkien culture. In addition to the words "lu" and "gue," there are also mentions of words from the name of the food that comes from the Hokkien language, such as meatballs, dumplings, spring rolls, capcai, tongseng. There are also mentions of nouns of objects or household furniture that come from the Hokkien language, for example, teapot, piso (knife), cup, duster, lonteng, and many more.Keywords: Hokkien; Fujian; Minnan; Language